A JUNIOR HIGH SCHOOL STUDENTS’ PERCEPTION TOWARD THE USE OF DUOLINGO AS A MALL (MOBILE-ASSISTED LANGUAGE LEARNING) FOR LEARNING ENGLISH GRAMMAR - Liwaurrohmah, Liwa Urrohmah (English Edu: Journal of English Teaching and Learning, 2023)
The purpose of this study is to describe how students’ perception on the using English learning media, especially cellular-based grammar using Duolingo, identify the advantages and disadvantages of the Duolingo application as a grammar learning medium and analyze what aspects have improved in students after using Duolingo as their learning medium. The subjects in this study were 30 first grade students at SMP X. The method used in this research is descriptive qualitative by describing the experiences that occur in the research subjects. The data was collected using a closed questionnaire filling technique and interviews with several randomly selected students and then the existing data was analyzed qualitatively with several steps; data reduction, data display, and drawing conclusions. The results of this study show; (1) students give positive perceptions in using Duolingo as their learning medium in two aspects, the first aspect is the effectiveness of Duolingo as a medium and their interest in using a medium. In terms of media effectiveness they feel that Duolingo is a medium that can be used anywhere and anytime. (2) Another finding indicated that students feel that there is a positive side of Duolingo where they can use it anywhere and anytime, but with a negative side in terms of internet connection. (3) The aspect that improves after students use Duolingo is that they feel more interested and motivated to use English in their daily lives.